Spiders of soybean crops in Santa Fe Province, Argentina: Influence of surrounding spontaneous vegetation on lot colonization - Beltramo, J. (2006)
Trials during two consecutive soybean cycles were performed in central Santa Fe in order to determine the main spider families present in the crop and to determine the influence of spontaneous margin flora on colonization towards the lot. Samplings were done by sweeping net and pitfall traps. It was concluded that: 1. Oxyopidae was the most frequent family in the herbaceous layer of both the margins and the soybean crop, and Lycosidae in the lower layer; 2. Margin strips in a soybean lot contribute to the colonization of the crop by spiders of aerial habits and also promote re-colonization following pesticide applications, since they act as shelters. The influence on spiders of terrestrial habits was somewhat lower; 3. The distribution of the populations of spiders of terrestrial habits was homogeneous in a soybean crop seeded directly and these predators had a greater capacity to control pests at all points of the lot.